Safety Profile of Caesalpinia spinosa Aqueous Extract Tested in Oreochromis niloticus Toward Its Application in Dermocosmetics - Salirrosas Fernández, Remigio David (2021)
The authors thank CONCYTEC-FONDECYT, process E041-01 (Contract number 123-2018-FONDECYT-BM-IADT/AV), and Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq, Process 305250/2019-1).